Information Resources for Forest Researchers and Managers: Strengths, Weaknesses, Threats and Opportunities. - Alan G. Brown; John W. Turnbull (Issues in Science and Technology Librarianship)
Pathways for the sharing and dissemination of information have been augmented significantly in the last decade by electronic tools for the reproduction, storage, transmission and retrieval of information. The Internet, through e-mail and chat rooms, assists personal informal communication. The greatest beneficiaries are workers in developed countries, where reliable high-speed networks, funding and other institutional factors encourage use of these tools. In developing countries, impediments to use of electronic communication include erratic power supplies, poor quality and limited availability of lines, environments destructive of electronic equipment, fees for access and downloading, and language barriers. Positive developments are the power of search engines now available, and the practices of some journals and publishers of making material (including abstracts) available at little or no cost, at least to users in developing countries. The ready global access to catalogues of major libraries, and effective and accessible abstracting services (e.g., Agricola, CAB Abstracts) have key roles. Unfortunately, some well-known services relevant to forestry have a heavy emphasis on northern hemisphere literature, are weak in coverage of social sciences and developing country and regional information, and expensive. Initiatives to bypass increasingly expensive journal publishers by open-access publishing on the web have had limited success, but open-access archiving is expanding quickly. Information dissemination and communication have been significantly improved by cheaper international travel, which has made face-to-face workshops and conferences far more accessible than in the past. The value of these occasions is maximised if the proceedings are reviewed, published promptly and cheaply, and fully analysed by abstracting services. Failure to publish proceedings, or to lodge published proceedings with major libraries or other accessible archives and abstracting services, is an opportunity lost. We challenge information professionals to improve the current position in this respect and, more broadly, to actively foster open-access archiving. The collation of research and operational experience, with a specific audience in mind, remains a key process for end users. In some situations, the primary difficulty end users face is to assess information relevance and develop solutions appropriate to their circumstances. Personal interaction between key field personnel and subject experts may be by far the most effective solution in such cases, being the means whereby field experience can be integrated with information readily available through the facilities in developed countries. Both cheaper travel and the Internet greatly assist this communication process. [ABSTRACT FROM AUTHOR]